2019
DOI: 10.15809/irriga.2019v24n2p236-253
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho Do Capim Tanzânia Irrigado Com Água Salobra Aplicada via Aspersão E Gotejamento

Abstract: DESEMPENHO DO CAPIM TANZÂNIA IRRIGADO COM ÁGUA SALOBRA APLICADA VIA ASPERSÃO E GOTEJAMENTO     SAULO SAMUEL CARNEIRO PRAXEDES1; MANOEL JANUÁRIO DA SILVA JÚNIOR2; JOSÉ FRANCISMAR DE MEDEIROS2; JOSÉ LEÔNCIO DE ALMEIDA SILVA3; FRANCISCO VALFISIO DA SILVA4 E ANA JAQUELINE DE OLIVEIRA TARGINO5   1Doutorando do PPGMSA, Universidade Federal Rural do Semi-Árido, UFERSA, Av. Francisco Mota, 572 - Bairro Costa e Silva, CEP: 59.625-900, Mossoró/RN/Brasil, saulosamuel@rn.gov.br; 2Depart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 5 publications
(5 reference statements)
1
8
0
1
Order By: Relevance
“…Lima et al (2018) described M. maximus as the most productive tropical forage propagated by seeds, being used worldwide due to its high productivity potential and forage quality, thus making room for study under salt stress conditions. Praxedes et al (2019), when evaluating the performance of the Tanzânia cultivar irrigated with saline water, did not observe tolerance of the cultivar to salinity above 2.8 dS/m, classifying it as moderately sensitive to irrigation water salinity. Salomón and Samudio (2015) found a reduction in germination speed and plant height of the Tanzânia and Mombaça cultivars with increasing salinity levels from 0.0 dS/m to 22.3 dS/m.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Lima et al (2018) described M. maximus as the most productive tropical forage propagated by seeds, being used worldwide due to its high productivity potential and forage quality, thus making room for study under salt stress conditions. Praxedes et al (2019), when evaluating the performance of the Tanzânia cultivar irrigated with saline water, did not observe tolerance of the cultivar to salinity above 2.8 dS/m, classifying it as moderately sensitive to irrigation water salinity. Salomón and Samudio (2015) found a reduction in germination speed and plant height of the Tanzânia and Mombaça cultivars with increasing salinity levels from 0.0 dS/m to 22.3 dS/m.…”
Section: Introductionmentioning
confidence: 77%
“…Similar results were found by Salomón and Samudio (2015), who observed a reduction of 15.0 and 10.0% in the germination percentage of the Mombaça and Tanzânia cultivars, respectively, under different levels of salt stress (ranging from 0.0 to 8.6 mS/cm) in irrigation water. Praxedes et al (2019) observed a decrease of 32% in the height of the Tanzânia cultivar for electrical conductivity of water (ECw) equal to 2.80 dS/m. The authors also observed a linear reduction in fresh mass with increasing salinity, at a ratio of 22.26 g for each unit increase in ECw, also classifying the cultivar as moderately sensitive to salinity.…”
Section: Resultsmentioning
confidence: 98%
“…Researchers attribute the reduced growth of plants irrigated with fi sh farming effl uent to the negative eff ects of the high salinity of the effl uents, since high salinity causes osmotic stress. As it reduces growth, it decreases the photosynthesis of plants due to the diff usion of CO 2 and changes in photosynthetic metabolism, such as oxidative stress, directly infl uencing growth (PRAXEDES et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…For being considered an essential food for consumption by the herd, pasture has been constantly improved in relation to seed selection, increased production and resistance to pests, especially in the arid and semi-arid regions of the world (GUILLAUME et al, 2021). Arid and semi-arid regions, due to the irregular distribution of rainfall, have concentrated pastures with lower yield and quality (PRAXEDES et al, 2019), making the management of water resources available and essential to reduce the problems caused by water scarcity and the consequent limitation in the yield of forage species (ROCHA FILHO et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A produção do capim Tanzânia pode variar conforme a composição do solo, espaçamento na qual foi plantado, altura do corte, lâmina de irrigação, entre outros. É comum encontrar, na literatura, produções variando de 2,16 a 3,42 t de MS.ha -1 (Macedo et al, 2017), até de 6,3 t de MS.ha -1 (Praxedes et al, 2019), utilizando irrigação. Legenda: kg = Quilograma; ha = hectare; UA = Unidade animal; 1 Com base na MS; Valores seguidos de mesma letra na linha, não diferem entre si pelo teste Tukey a 5%.…”
Section: Resultsunclassified